Analysis of the Poem "Keagungan Cinta" by Kahlil Gibran with an Objective Approach - Muhammad Endi Syaputra (Bulletin of Social Studies and Community Development, 2023)
Abstract: Poetry is a literary work that is formed by elements in it, so that it makes poetry beautiful and contains value and full of meaning. Intrinsic elements are elements that form a literary work derived from the literary text itself. The purpose of this study is to describe the intrinsic elements present in the poem” majesty of Love " by Kahlil Gibran using an objective approach study. The technique used by the author in collecting data is literature study with qualitative descriptive method. The results showed that the poem “majesty of Love” by Kahlil Gibran built by intrinsic elements in it, namely the inner elements (theme, taste, tone and mandate) and physical elements of poetry (including the choice of words, concrete words, images, figurative language or expression, rhyme and typography).   Keywords: poetry, objective, keagungan cinta